Iron-nickel composite three-dimensional porous electrode, preparation method thereof and application of iron-nickel composite three-dimensional porous electrode in electro-Fenton technology
By preparing iron-nickel composite three-dimensional porous electrodes, the problem of low degradation efficiency of pollutants in the electrofenton reaction is solved, the high conductivity and chemical stability of the electrode material are achieved, suitable for water pollution control, and material costs are reduced.
Patent Information
- Application Number
- CN202411613035.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The prior art is difficult to effectively improve the pollutant degradation efficiency in electrofenton reactions, and the conductivity and chemical stability of the electrode materials are insufficient, which limits its application in the field of water pollution control.
The Fe3NiN/FeS composite three-dimensional porous electrode is used to print the slurry containing iron, nickel, nitrogen and carbon sources into a three-dimensional structure, and high-temperature heat treatment is carried out under an ammonia atmosphere to form a Fe3NiN/FeS composite three-dimensional porous electrode, which improves the conductivity and chemical stability of the electrode.
It has achieved the improvement of pollutant degradation efficiency in electrofenton technology, and the electrode material has good conductivity and chemical stability. It is suitable for water pollution control, and has low cost and a wide range of materials.
Smart Images

Figure CN119638017A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of moldless direct writing technology, porous material preparation, electro-Fenton technology and material forming technology, and in particular to an iron-nickel composite three-dimensional porous electrode and a preparation method thereof and application in the electro-Fenton technology. Background Art
[0002] Direct ink writing (DIW) is an additive manufacturing technology that can quickly manufacture objects with complex geometric shapes. It uses computer drawing software to design a three-dimensional model, and deposits the slurry / ink with shear deformation ability layer by layer through computer-controlled movement of the printing needle to manufacture three-dimensional objects. DIW technology can replace printing needles of different sizes. Its accuracy mainly depends on the movement control of the printing needle and the three-dimensional platform, which can accurately control the accuracy and speed of printing. Therefore, the use of DIW technology can control the geometry and size of the electrode according to actual needs, which can effectively reduce material loss and control experimental costs.
[0003] Iron-based transition metal sulfides and nitrides have attracted extensive attention in the field of catalysis due to their wide range of raw material sources, high conductivity, abundant redox active centers, excellent mechanical stability, excellent thermal stability and stable catalytic performance. As an advanced electro-oxidation technology, electro-Fenton technology has achieved remarkable results in the field of water treatment. Its core is Fe 2+ It reacts with H2O2 to generate ·OH, which attacks pollutants in water and degrades them. The performance of bimetallic catalysts in pollutant degradation has important research value. The present invention constructs an electrode material composited with FeS and Fe3NiN to improve the efficiency of the electro-Fenton reaction. Summary of the invention
[0004] The purpose of the present invention is to provide an iron-nickel composite three-dimensional porous electrode, a preparation method thereof and an application in electro-Fenton technology. The method prints a three-dimensional structure of a slurry containing an iron source, a nickel source, a nitrogen source and a carbon source, and subjecting the material to a high-temperature heat treatment in an ammonia atmosphere to an oxidation-reduction reaction to generate a Fe3NiN / FeS composite three-dimensional porous electrode. The three-dimensional porous electrode has good electrical conductivity and chemical stability and can be applied to the field of water pollution control.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing an iron-nickel composite three-dimensional porous electrode, the method comprising the following steps:
[0007] (1) Raw material preparation: iron sulfate powder is used as an iron source, nickel sulfate is used as a nickel source, melamine powder and chitosan powder are used as carbon source and nitrogen source;
[0008] (2) Slurry preparation: iron sulfate powder, nickel sulfate powder, melamine powder, chitosan powder and an appropriate amount of deionized water are mixed and stirred until the mixture has a certain fluidity and no obvious agglomeration to obtain a printing slurry;
[0009] (3) 3D printing: the obtained slurry is loaded into a barrel and three-dimensionally molded using a screw extrusion 3D printer to obtain a three-dimensional wood pile structure blank;
[0010] (4) Heat treatment: drying the three-dimensional wood pile structure blank obtained in step (1), and subjecting the dried sample to high-temperature heat treatment to cause the raw materials in the three-dimensional wood pile structure to undergo oxidation-reduction reaction, thereby obtaining a Fe3NiN / FeS composite three-dimensional structure, i.e., the iron-nickel composite three-dimensional porous electrode.
[0011] Preferably, in step (1), the viscosity of the chitosan is 100-200 mPa.s or 200-400 mPa.s.
[0012] Preferably, in step (2), the weight ratio of the iron sulfate powder, nickel sulfate powder, melamine powder and chitosan powder is (12-18): (1-2): 3: 1.5.
[0013] Preferably, in step (3), the substrate (base) needs to be preheated before printing, and the printing substrate is a glass plate with transparent tape attached, and the preheating temperature is 40-50°C.
[0014] Preferably, in step (3), during printing, air pressure is applied to the barrel to allow the slurry to enter the screw extruder, and as the screw rotates, the slurry is extruded from the nozzle at a constant speed, and the printer needle moves at a constant speed to print the three-dimensional wood pile structure blank; wherein: the applied air pressure is about 0.2-0.4MPa, the screw extruder rotation extrusion ratio is 50-60%, and the printer needle movement speed is 800-1500mm / min.
[0015] Preferably, in step (4), the process of high temperature heat treatment is as follows: first, ammonia gas is passed through to exhaust for 0.5-1h, then the temperature is increased from room temperature to 750-850°C at a heating rate of 3-8°C / min and kept warm for 2-5 hours; after the insulation is completed, the temperature is naturally cooled to 150-250°C and then the ammonia gas is stopped, and then the temperature is naturally cooled to room temperature, the electrode is taken out for cleaning and drying.
[0016] The electrode cleaning process is: using deionized water to rinse and 95 vol.% ethanol to rinse the electrode three times in sequence; the drying process is drying in a forced air drying oven at 40° C. for 3-5 hours.
[0017] The above method is used to prepare an iron-nickel composite three-dimensional porous electrode, which is a three-dimensional porous structure composed of FeS and Fe3NiN. Carbon materials (elemental carbon and / or carbon compounds) are evenly distributed inside and on the surface of the three-dimensional porous structure skeleton; FeS is used as the main material of the electrode to maintain the stability of the three-dimensional structure and provide Fe 2+ The ions undergo electro-Fenton reaction; the uniform distribution of carbon materials improves the electrode conductivity and enhances the mechanical properties of the three-dimensional structure; Fe3NiN acts as an ion conductor to accelerate electron transfer and provide Ni 0 Participate in the electro-Fenton reaction.
[0018] The iron-nickel composite three-dimensional porous electrode is used as a cathode in the electro-Fenton technology.
[0019] The design ideas of the present invention are as follows:
[0020] In the composite material electrode constructed by the present invention, FeS is used as the main electrode material to provide Fe 2+ Participate in the electro-Fenton reaction; Fe3NiN has excellent conductivity and contains Ni 0 The following reaction occurs in the system: Ni 0 +2O2→Ni 2+ +2·O2 - Provide superoxide free radicals and increase the production of H2O2, thereby effectively improving the efficiency of the electro-Fenton reaction.
[0021] Specifically, the redox reaction between iron sulfate, nickel sulfate and ammonia will form Fe3NiN and FeS composite materials. The core of electro-Fenton technology is Fe 2+ It reacts with H2O2 to form ·OH, which degrades the macromolecular structure into small molecular structures or H2O and CO2, so it has important research value in the field of water treatment. The use of iron sulfate, nickel sulfate, melamine, and chitosan powder mixed into a slurry can provide a nitrogen source inside the material to ensure that the three-dimensional structure can fully react inside and outside. After the carbon source is decomposed, a carbon layer or a carbon material skeleton is formed in the three-dimensional structure, which can strengthen the structural stability and enhance the conductivity of the three-dimensional electrode. In addition, during the reaction process, due to the generation and flow of gas, pores will be formed inside and outside the three-dimensional electrode, forming an interconnected three-dimensional porous structure, which can expose more active sites, increase the reaction area, and improve the reaction efficiency.
[0022] The advantages and beneficial effects of the present invention are as follows:
[0023] 1. The present invention mixes iron source, nickel source, nitrogen source and carbon source powders in a ball mill, adds an appropriate amount of water and stirs them into a slurry that can be three-dimensionally formed, constructs a three-dimensional structure using a 3D printer, and performs high-temperature heat treatment under an ammonia atmosphere to cause the material to undergo an oxidation-reduction reaction to generate a Fe3NiN / FeS composite three-dimensional porous electrode. The three-dimensional porous electrode has good electrical conductivity and chemical stability, and can be applied to the field of water pollution control, specifically as an electro-Fenton cathode material to remove pollutants. In addition, since the carbon material is widely and evenly present in the three-dimensional structure, the electrical conductivity and stability of the three-dimensional electrode can be improved.
[0024] 2. The preparation method of the three-dimensional porous electrode of the present invention is simple, and the raw materials used are widely available and cheap, which can effectively reduce material costs in practical applications.
[0025] 3. When the raw material powder used in the present invention reacts in an ammonia atmosphere, gas will be generated, and pores will be formed inside and outside the three-dimensional structure to form a three-dimensional porous structure. Therefore, it can effectively increase the reaction area of the material and expose more active sites. Compared with the two-dimensional planar electrode, it has a significant improvement. Therefore, the method of the present invention can be widely used in the preparation of electrode materials such as catalysis and energy storage.
[0026] 4. The three-dimensional porous electrode of the present invention has a significant removal effect on common water pollutants. The reaction process is: O2+2H + +2e - →H2O2;Fe 2+ +H2O2→Fe 3+ + OH+OH - ; RH+·OH→R+H2O, where RH macromolecules contain pollutants, and R is a small molecule or CO2. The electro-Fenton reaction does not produce secondary pollutants, and the content of iron and nickel ions in the water body during the reaction is extremely low. It is an environmentally friendly electrode material with important potential for wide application.
[0027] 5. The method for preparing slurry of the present invention can select suitable materials to synthesize three-dimensional electrodes, and form pores on the surface and inside of the three-dimensional electrodes in combination with a heat treatment process, thereby preparing a three-dimensional porous electrode with a macroscopic three-dimensional structure and a microscopic three-dimensional porous structure. The three-dimensional electrode synthesized in this way has a larger specific surface area and higher porosity, which can effectively shorten the transmission distance of ions to increase the reaction rate and reduce energy consumption, and has more active sites, which helps to improve performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XRD result of the Fe3NiN / FeS composite electrode prepared after high-temperature heat treatment in ammonia in step (3) of Example 1-2.
[0029] Figure 2 Optical photographs of the three-dimensional structure blanks printed with slurries containing different amounts of nickel sulfate in Examples 1-2 before and after heat treatment; wherein: (a) Example 1 blank before heat treatment; (b) Example 1 blank after heat treatment; (c) Example 2 blank before heat treatment; (d) Example 2 blank after heat treatment.
[0030] Figure 3 Field emission scanning electron microscope morphology and energy spectrum scanning photo of the Fe3NiN / FeS composite three-dimensional porous electrode prepared in Example 1-2; wherein: (a) Example 1; (b) Example 2.
[0031] Figure 4 The light absorption curves of the two Fe3NiN / FeS composite three-dimensional porous electrodes prepared in Examples 1-2 in the degradation experiment of 5 ppm RhB (Rhodamine B) using the electro-Fenton technology.
[0032] Figure 5 The experimental results of the degradation of 15 ppm TC-HCl in different water environments using the Fe3NiN / FeS composite three-dimensional porous electrode prepared in Example 3 and the electro-Fenton method are shown.
[0033] Figure 6 The leakage of iron and nickel ions from the three difficult electrodes in Example 3 during the electro-Fenton reaction. DETAILED DESCRIPTION
[0034] The present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0035] The present invention comprises the following steps: uniformly mixing iron source, nitrogen source and carbon source powders in a ball mill and then taking them out; adding an appropriate amount of deionized water to dissolve a nickel source in a mortar; then adding the ball-milled powder and stirring to form a three-dimensionally formed slurry; and using an extrusion 3D printer to perform three-dimensional molding to construct different three-dimensional structures; and then performing high-temperature heat treatment in an ammonia atmosphere. After the raw materials react, a Fe3NiN and FeS two-phase composite electrode is generated. Furthermore, due to the participation and generation of gas in the reaction process, pores are formed inside and outside the three-dimensional electrode to form a three-dimensional porous electrode, thereby exposing more reaction active sites and increasing the reaction area.
[0036] The iron source used is ferric sulfate powder, the nickel source is nickel sulfate powder, the nitrogen source is melamine powder, the carbon source is chitosan powder, the viscosity of the chitosan powder is 100-200mpa.s or 200-400mpa.s, and all the chemicals used are analytically pure.
[0037] The cleaning and drying process in the following examples is: rinsing the three-dimensional electrode with deionized water and 95 vol.% ethanol three times in sequence; the drying process is drying in a forced air drying oven at 50° C. for 3-5 hours.
[0038] Embodiment 1-2:
[0039] This example is to prepare a Fe3NiN / FeS three-dimensional porous electrode, and use the electrode to degrade 5ppm RhB (Rhodamine B dye) by the electro-Fenton method. The specific process is as follows:
[0040] (1) 15 g of iron sulfate powder, 3 g of melamine powder and 1.5 g of chitosan powder were mixed in a ball mill for 4 hours and then taken out. 1 g or 2 g of nickel sulfate was placed in a mortar and an appropriate amount of deionized water was added to stir and dissolve. Then, the ball-milled powder was added and stirred to form a slurry with a certain fluidity. The slurry was loaded into a barrel for printing. The composition of each raw material powder in the slurry is shown in Table 1.
[0041] Table 1
[0042] sample Ferrous Sulfate Nickel sulfate Melamine Chitosan Example 1 15g 1g 3g 1.5g Example 2 15g 2g 3g 1.5g
[0043] (2) The substrate was preheated to 50°C in advance during printing, and the printing substrate was a glass plate with transparent tape attached. During printing, 0.4 MPa of air pressure was applied to the barrel to allow the slurry to enter the screw extruder at a uniform speed. As the screw rotated, the slurry was extruded from the nozzle at a constant speed, and the printer needle moved at a uniform speed to print the three-dimensional wood pile structure blank; the screw extruder rotation extrusion ratio was set to 50%, and the printer needle movement speed was set to 1200 mm / min; the printing size of the three-dimensional wood pile structure was 1.2×1.2×0.6 cm.
[0044] (3) After printing, the obtained three-dimensional wood pile structure blank was placed in an oven and dried at 40°C for 4 hours, then placed in a tubular furnace and connected to ammonia, and the air was exhausted for 30 minutes, and then heated to 800°C at a heating rate of 5°C / min and kept warm for 3 hours. When the temperature naturally cooled to 200°C, the introduction of ammonia was stopped, and then naturally cooled to room temperature and taken out. The three-dimensional electrode was rinsed with deionized water and 95 vol.% ethanol for 3 times, and placed in an oven and dried at 40°C for 5 hours to obtain an iron-nickel composite three-dimensional porous electrode (Fe3NiN / FeS composite electrode). The electrode size obtained after heat treatment was about 0.6×0.6×0.3 cm.
[0045] The prepared electrode was used as cathode and the platinum sheet electrode as anode, and 5 ppm RhB (rhodamine B dye) was degraded by electro-Fenton method.
[0046] Figure 1The XRD results of the Fe3NiN / FeS composite electrode prepared after high-temperature heat treatment in ammonia in step (3) are shown. From the XRD results, it can be seen that Examples 1-2 with different amounts of nickel sulfate added all formed a two-phase structure of Fe3NiN and FeS (corresponding to the standard PDF card), and the carbon source decomposed at 800°C to form a single carbon that is evenly distributed in the three-dimensional structure electrode skeleton, further strengthening the stability of the three-dimensional electrode structure and enhancing its conductivity.
[0047] Figure 2 The optical photos of the three-dimensional structure blank printed with nickel-iron sulfate slurry in step (3) before and after the heat treatment reaction are shown. It can be seen that the three-dimensional structure after the heat treatment maintains the original design structure and has good mechanical stability.
[0048] Figure 3 The field emission scanning electron microscope photographs of the Fe3NiN / FeS composite three-dimensional porous electrode prepared by printing and heat treatment of slurry with different amounts of nickel sulfate added show that there are extensive holes distributed in the electrode, which is caused by the generation of gas during the reaction and the reaction inside the material. The three-dimensional electrode maintains the original printed structure and has good structural stability.
[0049] Figure 4 This is the light absorption curve of the 5 ppm RhB degradation experiment using the electro-Fenton method. It can be seen that the two Fe3NiN / FeS electrodes prepared in Examples 1-2 have obvious degradation effects on RhB and do not produce other pollutants during the degradation process.
[0050] Example 3
[0051] This example is to prepare a Fe3NiN / FeS composite three-dimensional porous electrode and use the electro-Fenton method to degrade 15ppm TC-HCl, i.e. tetracycline hydrochloride, an antibiotic. The specific process is as follows:
[0052] 1) Take 15 grams of iron sulfate powder, 5 grams of melamine powder and 1.5 grams of chitosan powder and stir them in a ball mill for 4 hours, then take them out, add 1 gram of nickel sulfate and appropriate amount of deionized water to dissolve them in a mortar, then add the ball-milled powder and stir to form a slurry with a certain fluidity, and load the slurry into a barrel for printing;
[0053] (2) Preheat the substrate to 45-50°C in advance during printing. The printing substrate is glass with transparent tape attached. The air pressure is set to 0.4 MPa during printing so that the slurry enters the screw at a uniform speed. Set the printing speed and base rate for printing.
[0054] (3) After printing, the sample was placed in an oven and dried at 40°C for 4 hours, then placed in a tubular furnace and connected to ammonia, the air was exhausted for 30 minutes, and then heated to 800°C at a heating rate of 5°C / min and kept warm for 3 hours. When the temperature naturally cooled to 200°C, the introduction of ammonia was stopped, and the sample was taken out after naturally cooling to room temperature. The three-dimensional electrode was rinsed with deionized water and 95 vol.% ethanol three times in sequence, and placed in an oven and dried at 40°C for 5 hours to obtain a Fe3NiN / FeS composite three-dimensional porous electrode.
[0055] (4) The prepared electrode was used as the cathode and the platinum electrode as the anode, and the electro-Fenton method was used to degrade tetracycline hydrochloride (TC-HCI) in the water environment.
[0056] Figure 5 The results of the degradation experiment of 15ppm TC-HCI in different water environments (deionized water and tap water) using the electro-Fenton method are shown. It can be clearly seen that the concentration of TC-HCI gradually decreases as the experiment proceeds, and it has a good degradation effect in different water environments. Fe3NiN / FeS, as the cathode material in the electro-Fenton method, has a wide range of degradation effects on common pollutants and has practical application value.
[0057] Figure 6 This is the leakage amount of iron and nickel ions of the electrode material in Example 3 during the electro-Fenton reaction. It can be seen that the content of iron and nickel ions in the water body is extremely low during the degradation reaction.
[0058] The present invention includes but is not limited to the above embodiments. Any equivalent replacement or partial improvement made under the principle of the spirit of the present invention shall be deemed to be within the protection scope of the present invention.
Claims
1. A method for preparing an iron-nickel composite three-dimensional porous electrode, characterized in that: The method comprises the following steps: (1) Raw material preparation: iron sulfate powder is used as an iron source, nickel sulfate is used as a nickel source, melamine powder and chitosan powder are used as carbon source and nitrogen source; (2) Slurry preparation: iron sulfate powder, nickel sulfate powder, melamine powder, chitosan powder and an appropriate amount of deionized water are mixed and stirred until the mixture has a certain fluidity and no obvious agglomeration to obtain a printing slurry; (3) 3D printing: the obtained slurry is loaded into a barrel and three-dimensionally molded using a screw extrusion 3D printer to obtain a three-dimensional wood pile structure blank; (4) Heat treatment: drying the three-dimensional wood pile structure blank obtained in step (1), and subjecting the dried sample to high-temperature heat treatment to cause the raw materials in the three-dimensional structure to undergo oxidation-reduction reaction, thereby obtaining the iron-nickel composite three-dimensional porous electrode (Fe3NiN / FeS composite three-dimensional electrode).
2. The method for preparing the iron-nickel composite three-dimensional porous electrode according to claim 1, characterized in that: In step (1), the viscosity of the chitosan is 100-200 mPa.s or 200-400 mPa.s.
3. The method for preparing the iron-nickel composite three-dimensional porous electrode according to claim 1, characterized in that: In step (2), the weight ratio of the iron sulfate powder, nickel sulfate powder, melamine powder and chitosan powder is (12-18): (0.5-2.5): (2.5-6.5): (1-3).
4. The method for preparing the iron-nickel composite three-dimensional porous electrode according to claim 1, characterized in that: In step (3), the substrate (base) needs to be preheated in advance before printing. The printing substrate is a glass plate with transparent tape attached, and the preheating temperature is 40-50°C.
5. The method for preparing the iron-nickel composite three-dimensional porous electrode according to claim 1, characterized in that: In step (3), during printing, air pressure is applied to the barrel to allow the slurry to enter the screw extruder, and as the screw rotates, the slurry is extruded from the nozzle at a constant speed, and the printer needle moves at a constant speed to print the three-dimensional wood pile structure blank; wherein: the applied air pressure is about 0.2-0.4MPa, the screw extruder rotation extrusion ratio is 50-60%, and the printer needle movement speed is 800-1500mm / min.
6. The method for preparing the iron-nickel composite three-dimensional porous electrode according to claim 1, characterized in that: In step (4), the high temperature heat treatment process is as follows: first, ammonia gas is exhausted for 0.5-1h, then the temperature is increased from room temperature to 750-850°C at a heating rate of 3-8°C / min and kept at this temperature for 2-5 hours; After the insulation is completed, the electrode is naturally cooled to 150-250°C and then the introduction of ammonia is stopped. The electrode is then naturally cooled to room temperature and the electrode is taken out for cleaning and drying.
7. An iron-nickel composite three-dimensional porous electrode prepared by the method described in claims 1-7.
8. The iron-nickel composite three-dimensional porous electrode according to claim 7, characterized in that: The iron-nickel composite three-dimensional porous electrode is a three-dimensional porous structure composed of FeS and Fe3NiN. Carbon materials (single carbon and / or carbon compounds) are evenly distributed inside and on the surface of the three-dimensional porous structure skeleton. Among them, FeS is used as the main material of the electrode to maintain the stability of the three-dimensional structure and provide Fe 2+ The ions undergo electro-Fenton reaction; the uniform distribution of carbon materials improves the electrode conductivity and enhances the mechanical properties of the three-dimensional structure; Fe3NiN acts as an ion conductor to accelerate electron transfer and provide Ni 0 Participate in the electro-Fenton reaction.
9. The use of the iron-nickel composite three-dimensional porous electrode in the electro-Fenton technology according to claim 7, characterized in that: The iron-nickel composite three-dimensional porous electrode is used as a cathode in the electro-Fenton technology.
Citation Information
Patent Citations
Methods of fabricating laser-induced graphene and compositions thereof
CN110167877A
Preparation method and application of heterogeneous electro-Fenton bifunctional cathode material
CN115893598A
Nitrogen-metal doped three-dimensional porous carbon material and preparation method and application thereof
CN117059403A
Catalyst including sulfated transition metal oxides and used for electro-fenton system, electrode including the catalyst, and electro-fenton system using the electrode
US20200190677A1
Processes for electrochemical up-cycling of plastics and systems thereof
US20230304170A1